Epidemiological characteristics of post-traumatic stress symptoms and its influence on length of hospital stay in inpatients with traumatic fractures in Zunyi, China - Guojia Qi; Xiu Dai; Xue Wang; Ping Yuan; Xiahong Li; Miao Qi; Xiuli Hu; Xiuquan Shi (AIMS Press, 2024)
Objectives To investigate the clinical epidemiological characteristics and occurrence of post-traumatic stress symptoms (PTSS) in patients with traumatic fractures, we sought to analyze the factors that influence the prognosis of a length of hospital stay (LOS) and provide valuable insights to prevent PTSS in fracture patients and improve their prognosis. Methods Inpatients with traumatic fractures were recruited from a third-class comprehensive general hospital in southwest China between November 2019 and October 2020. Case data of traumatic fracture patients were collected, and a questionnaire that included general information and basic fracture details was completed. The post-traumatic stress disorder Self-rating Scale was used to assess PTSS among the fracture inpatients. Results A total of 204 inpatients who experienced traumatic fractures were included in this study. Falls accounted for the largest proportion of traumatic fractures. A Cox's regression analysis revealed that serious injury [Hazard Ratio (HR) = 2.44, 95% Confidence Interval (CI): 1.33-4.46], critical illness during hospitalization (HR = 1.70, 95% CI: 1.13-2.54), and undergoing two surgeries (HR = 1.87, 95% CI: 1.20-2.93) were risk factors for longer LOS. Among the fracture patients, 30.39% exhibited positive PTSD symptoms, and physical activity during the fracture [Odds Ratio (OR) = 0.63, 95% CI: 0.45-0.88] and increased pain (OR = 3.34, 95% CI: 1.82-6.11) were identified as influencing factors. Conclusions Given the high detection rate of PTSS following traumatic fractures, it is crucial for relevant departments to implement targeted measures to protect high risk individuals. Furthermore, strengthening the care provided to the patients' physical and mental health is urgently needed to reduce the incidence of PTSS.